Step-by-step explanation:
3×3×3=27.
hope this helps you.
Answer:
c. (3, 2)
Step-by-step explanation:
Equating the values of y :
- -x + 5 = x - 1
- x + x = 5 + 1
- 2x = 6
- <u>x = 3</u> [x-coordinate of the solution]
Finding y by substituting x in one of the equations :
- y = x - 1
- y = 3 - 1
- <u>y = 2</u> [y-coordinate of the solution]
Solving :
- Solution = (x, y)
- Solution = (3, 2)
It goes straight sideways
Answer: I don't see anything. Maybe upload some images?
Step-by-step explanation:
The answer would be 95/100 = 0/100 I hope this helped ^^